The ideological roots of institutional change - Iyigun, Murat; Rubin, Jared (Bonn, 2017)
"Why do some societies fail to adopt more efficient institutions in response to changing economic conditions? And why do such conditions sometimes generate ideological backlashes and at other times lead to transformative sociopolitical movements? We propose an explanation that highlights the interplay – or lack thereof – between new technologies, ideologies, and institutions. When new technologies emerge, uncertainty results from a lack of understanding how the technology will fit with prevailing ideologies and institutions. This uncertainty discourages investment in institutions and the cultural capital necessary to take advantage of new technologies. Accordingly, increased uncertainty during times of rapid technological change may generate an ideological backlash that puts a higher premium on traditional values. We apply the theory to numerous historical episodes, including Ottoman reform initiatives, the Japanese Tokugawa reforms and Meiji Restoration, and the Tongzhi Restoration in Qing China."